An investigation of the influencing elements and impact of big data analytics on supply chain performance - Priti P Kohale, Dr. Shailja Sharma, Dr Narendra Chaudhari, (Design Engineering, 2022)
The purpose of this study is to comprehend how big data analytics has changed the supply chain for retail establishments. We design our framework to choose the finest big data techniques from a range of options based on the effectiveness of the retailing sector. We used TODIM, which stands for Portuguese Interactive Multi-Criteria Decision Making, to choose the best tools for big data analytics from the nine practices. One of the research's noteworthy findings is that most retail organizations find it difficult to balance expenses and customers when using big data approaches. In this study, the use of big data approaches to the retail supply chain is examined. Considering the supply chain's performance, as well as the best big data techniques.